Microvascular effects of the inhibition of dipeptidylpeptidase IV by linagliptin in nondiabetic hypertensive patients - Forst, Thomas; Michelson, Georg; Diessel, Stephan; Jahnke, Johannes; Kapitza, Christoph (Journal of Hypertension, 2016)
Recent studies suggest vascular benefits of dipeptidylpeptidase IV (DPP-IV) inhibition in patients with diabetes mellitus. Only little is known about potential vascular effects of DPP-IV inhibitors in nondiabetic individuals. The aim of this study was to investigate the effect of DPP-IV inhibition in a nondiabetic hypertensive population.This was a double-blinded, randomized, placebo-controlled, mechanistic study, comparing microvascular effects of the DPP-IV inhibitor linagliptin with placebo in nondiabetic individuals with a history of arterial hypertension. Twenty-one patients received 5 mg linagliptin (5 women; age 67.6 ± 6.0 years; mean ± SD), whereas 22 patients were randomized to placebo (5 women; age 64.8 ± 7.1 years).At baseline, after 6 and 12 weeks, retinal microcirculation and arterial blood pressure profiles were assessed. Moreover, blood samples were taken for the measurement of HbA1c, asymmetric dimethylarginine, C-reactive peptide, cyclic guanosinmonophosphate, transforming growth factor beta (TGF-ß1) and cystatin C. Retinal capillary perfusion increased by 23.7 ± 10.3% (mean ± SEM; P < 0.05), retinal arterial flow by 7.6 ± 0.6 (P < 0.05) and the retinal hyperemic response by 290 ± 263% (P < 0.05) during treatment with linagliptin. No change in retinal blood flow was found in the placebo group. Although blood pressure declined in both groups, a significant decline in TGF-ß1 by 9.3 ± 4.5% (P < 0.05) could only be observed in the linagliptin group. No significant change in other laboratory parameters could be observed in both groups.Our study suggests microvascular and antifibrotic effects of linagliptin in a nondiabetic, hypertensive population.
EVALuna2:21245